Activation of cGMP/Protein Kinase G Pathway in Postconditioned Myocardium Depends on Reduced Oxidative Stress and Preserved Endothelial Nitric Oxide Synthase Coupling. Issue 1 (2nd January 2013) - Inserte, Javier; Hernando, Victor; Vilardosa, Úrsula; Abad, Elena; Poncelas‐Nozal, Marcos; Garcia‐Dorado, David
Abstract : Background: The cGMP/protein kinase G (PKG) pathway is involved in the cardioprotective effects of postconditioning (PoCo). Although PKG signaling in PoCo has been proposed to depend on the activation of the phosphatidylinositol 3‐kinase (PI3K)/Akt cascade, recent data bring into question a causal role of reperfusion injury signaling kinase (RISK) in PoCo protection. We hypothesized that PoCo increases PKG activity by reducing oxidative stress–induced endothelial nitric oxide synthase (NOS) uncoupling at the onset of reperfusion. Methods and Results: Isolated rat hearts were submitted to 40 minutes of ischemia and reperfusion with and without a PoCo protocol. PoCo reduced infarct size by 48% and cGMP depletion. Blockade of cGMP synthesis (1 H ‐[1, 2, 4]oxadiazolo[4, 3‐a ]quinoxalin‐1‐one) and inhibition of PKG (KT5823) or NOS (l ‐NAME) abolished protection, but inhibition of PI3K/Akt cascade (LY294002) did not (n=5 to 7 per group). Phosphorylation of the RISK pathway was higher in PoCo hearts. However, this difference is due to increased cell death in control hearts because in hearts reperfused with the contractile inhibitor blebbistatin, a drug effective in preventing cell death at the onset of reperfusion, RISK phosphorylation increased during reperfusion without differences between control and PoCo groups. In these hearts, PoCo reduced the production of superoxide (O2 − ) and protein nitrotyrosylation and increased nitrate/nitrite levels in parallel with a significant decrease in the oxidation of tetrahydrobiopterin (BH4 ) and in the monomeric form of endothelial NOS. Conclusions: These results demonstrate that PoCo activates the cGMP/PKG pathway via a mechanism independent of the PI3K/Akt cascade and dependent on the reduction of O2 − production at the onset of reperfusion, resulting in attenuated oxidation of BH4 and reduced NOS uncoupling.